Association Between Arsenic Toxicity, AS3MT Gene Polymorphism and Onset of Type 2 Diabetes - Shokat, Saima; Iqbal, Riffat; Riaz, Samreen; Yaqub, Atif (Biological trace element research, 2024)
Arsenic (As) exposure in drinking water has become a serious public health issue. AS3MT gene is involved in the metabolism of arsenic, so a single nucleotide polymorphism in this gene may lead to the development of type 2 diabetes in arsenic-exposed areas. This study aimed to evaluate the association of the AS3MT gene with the development of type 2 diabetes in highly arsenic-exposed areas of Punjab, Pakistan. Total 200 samples equal in number from high arsenic exposed-areas of Lahore (Nishtar) and Kasur (Mustafa Abad) were collected. rs11191439 was utilized as an influential variable to evaluate the association between arsenic metabolism and diabetes status to find a single nucleotide polymorphism in the AS3MT gene. We observed the arsenic level in drinking water of the arsenic-exposed selected areas 115.54 ± 1.23 µg/L and 96.88 ± 0.48 µg/L, respectively. The As level in the urine of diabetics (98.54 ± 2.63 µg/L and 56.38 ± 12.66 µg/L) was higher as compared to non-diabetics (77.58 ± 1.8 µg/L and 46.9 ± 8.95 µg/L) of both affected areas, respectively. Correspondingly, the As level in the blood of diabetics (6.48 ± 0.08 µg/L and 5.49 ± 1.43 µg/L) and non-diabetics (6.22 ± 0.12 µg/L and 5.26 ± 0.24 µg/L) in the affected areas. Genotyping showed significant differences in the frequencies of alleles among cases and controls. Nevertheless, notable disparities in genotype distribution were observed in SNPs rs11191439 (T/C) ( P < 0.05) and when comparing T2D patients and non-diabetic control subjects. The AS3MT gene and clinical parameters show a significant association with the affected people with diabetes living in arsenic-exposed areas.